Control with Constraints for Multivariable Objects with Time Delay. Issue 12 (2016) - Yakovis, Leonid; Sporyagin, Kirill; Chechurin, Leonid
Abstract: Methods for parametric design of standard controllers for multivariable dynamic objects with time delay are presented. This methods enable approximate control quality optimization with various criteria in the case of interconnected and multivariable plant with control constraints. Adaptive tuning algorithm for standard controller adjustment is presented. The study presents a software prototype for automated controller design.